The New Transatlantic Relations and the Perspectives of the Global Order. Proceedings of the first edition of the international conference The European Union’s External Relations and the Global Order (EUXGLOB) - NAUMESCU, Valentin; MOLDOVAN, Raluca; GHILESCU, Anda (Presa Universitară Clujeană, 2021)
The first edition of the international conference EUXGLOB (The European Union’s External Relations and the Global Order) took place on April 15, 2021. The conference was organized by the EUXGLOB Center at the Faculty of European Studies of Babeș‐Bolyai University Cluj Napoca. The welcome speeches were delivered by the Rector of Babeș‐Bolyai University, professor Daniel David, and the Dean of the Faculty of European Studies, associate professor Adrian Gabriel Corpădean. We were also honored that the series of EUXGLOB Conferences was officially inaugurated by the opening speech of H.E. Klaus Werner Iohannis, the President of Romania.